Influence Of Product Quality On Company Image In PT. The Eternal Holy Mountain Of Medan - Ingatan Laia (JURNAL ILMIAH SOCIO SECRETUM, 2022)
Product quality is the overall characteristics and characteristics of service products that support the ability to satisfy needs. Meanwhile, corporate image is the impression, feeling, image of the community or the public towards the company, an impression that is intentionally created from a product or service offered. The formulation of the problem in this study is "Does Product Quality Affect Company Image At PT. The Eternal Sacred Mountain of Medan?” The framework of thinking in this study consists of two variables, namely: Variable X (Product Quality) and Variable Y (Company Image). The population of this study is a number of consumers who regularly buy PT. The Eternal Sacred Mountain of Medan. The sample amounted to 67 respondents and the data collection techniques in this study were a list of questions (questionnaires) and interviews. The data analysis technique used is simple linear regression analysis using SPSS 22 Windows. From the results of the regression equation obtained, namely: Y = 16.275 + 0.254 X. based on the coefficient of determination R ^ 2 = 80.6%, it means that the contribution given by Product Quality to Company Image is 80.6% and the remaining 19.4% is influenced by factors -other factors that were not included in this study, such as price, brand and so on. Based on the results of the statistical test (t test), the value of t count > t table (4.190>1.997) with a significant level of 0.000 <0.05). So it can be concluded that the hypothesis in this study is "Product Quality has a significant effect on Corporate Image at PT. Medan's Eternal Sacred Mountain". It is suggested to the company to maintain good product quality because with the support of affordable product quality, because these variables have a positive and significant effect on corporate image.